Evaluation of Ciprofloxacin Degradation during Composting Process - Ahmad Jonidi Jafari; Mahdi Farzadkia; Mitra Gholami; mina mohagheghi (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: The growing trend of using antibiotics to control human and animal diseases and lack of attention to the disposal of medical, hospital, and pharmaceutical industry wastes have led to the emergence of environmental problems. regarding this, the present study was conducted to determine the antibiotic degradation of ciprofloxacin during the composting process. Methods: The present experimental study was conducted using a mixture of livestock manure, fruit residue, straw, and sludge to prepare compost over 40 days. Ciprofloxacin was added to the compost reactors at three concentrations of 20, 50, and 100 mg/kg. The temperature, humidity, carbon to nitrogen ratio, and pH of the compost were monitored, and reactor sampling was performed weekly. The analysis of antibiotics was accomplished using a high-performance liquid chromatography. The data were analyzed through the one-way ANOVA in the SPSS software (version 22). Results: According to the results, the rates of ciprofloxacin degradation at day 21 and end of the thermophilic phase were 89.47, 88.81, and 86.46% in reactors 20, 50, and 100 mg/kg, respectively. At the end of the process, all three reactors had the removal rate of 99.99%. Moreover, the physio-chemical properties of the final compost were within the national standard. Conclusion: As the findings indicated, the use of aerobic composting process to degrade ciprofloxacin is an economical, effective, and environmentally friendly method. Accordingly, at the end of the process, 99.99% of ciprofloxacin was degraded.